Conditions of warm ausforming of low-alloy medium-carbon steel for making fully martensitic microstructure and its refining effect of martensite. (March 2021) - Niho, Takayoshi; Nambu, Shoichi; Nagato, Keisuke; Nakao, Masayuki
Graphical abstract: Abstract: This study elucidates the process conditions of ausforming low-alloy medium-carbon steel that can be used to make a fully martensitic microstructure. In the process, the austenitized steel at a high temperature is cooled to warm temperature kept in the supercooled austenite state, then deformed and quenched. The result of this study indicates that the duration time needs to be shortened sufficiently, because supercooled austenite of low-alloy steel only exists for a few seconds. The change of martensitic microstructure is also investigated. Originally, microstructure of low-alloy medium-carbon steel martensite consists of fine lath and coarse butterfly martensite. The frequency of coarse butterfly martensite is decreased by ausforming but is not zero for lower strain levels; coarse butterfly martensite does not form at higher strain levels. This change is presumed to be caused by lattice defects introduced into the austenite matrix by ausforming. In this research, changes in the martensite block width and hardness are investigated. The hardness increases as the block width decreases.